Nonlinear Conte-Zbilut-Federici (CZF) Method of Computing LF/HF Ratio: A More Reliable Index of Changes in Heart Rate Variability - Vernon Bond Jr; Bryan H Curry; Krishna Kumar; Sudhakar Pemminati; Vasavi R Gorantla; Kishan Kadur; Richard M Millis (Korean Pharmacopuncture Institute, 2016)
Objectives: Acupuncture treatments are safe and effective for a wide variety of diseases involving autonomic dysregulation. Heart rate variability (HRV) is a noninvasive method for assessing sympathovagal balance. The low frequency/high frequency (LF/HF) spectral power ratio is an index of sympathovagal influence on heart rate and of cardi